Traditional and novel non-statin lipid-lowering drugs - Peeyush Jain (Indian Heart Journal, 2024)
Non-statin drugs find utility in the management of dyslipidaemia in mixed dyslipidaemia, patients with statin intolerance, and when guidelines directed low-density lipoprotein cholesterol (LDL-C) target cannot be achieved despite maximally tolerated statin. The most definite indication of fenofibrate monotherapy is fasting serum triglyceride >500 mg/dl to reduce the risk of acute pancreatitis It offers a modest reduction in cardiovascular events. The statin-ezetimibe combination is commonly used for lipid lowering particularly after ACS. Fish oils reduce serum triglycerides by about 25 %. EPA (and not DHA) seems to have cardioprotective effects. Despite cardiovascular outcome benefits, bile-exchange resins have limited use due to poor tolerance. Bempedoic acid added to maximally tolerated statin therapy is approved to lower LDL-C in adults with primary hypercholesterolemia or mixed dyslipidaemias, HeFH, in patients with ASCVD who require additional lowering of LDL-C, and in patients who are statin-intolerant. Inclisiran is a long-acting double-stranded small interfering RNA (siRNA) that inhibits the transcription of PCSK-9 leading to a decrease in PCSK9 generation in hepatocytes and an increase in LDL receptor expression in the liver cell membrane leading to about 50 % reduction in serum LDL-C levels. Lomitapide lowers plasma levels of all ApoB-containing lipoproteins, including VLDL, LDL, and chylomicrons by inhibiting the enzyme microsomal triglyceride transfer protein (MTP) and approved for the treatment of adult patients with homozygous familial hypercholesterolemia (HoFH). Close monitoring for hepatotoxicity is required. Mipomersen is a single-stranded synthetic antisense oligonucleotide (ASO) that affects the production and secretion of apoB-containing lipoproteins with demonstrated efficacy in both homozygous and heterozygous FH patients. It is approved for restricted use due to risk of hepatotoxicity. Pelacarsen is an antisense oligonucleotide that reduces the production of apo(a) in the liver.